4CPS-018 Evaluation of antiplatelet agent prescribing in patients on direct oral anticoagulant. (March 2019) - Larock, AS; Spinewine, A; Laloux, P; Eucher, P; Hanet, C
Abstract : Background: Among patients requiring an oral anticoagulant (OAC), a large proportion also take an antiplatelet agent (AP). Several studies have highlighted the significantly increased bleeding risk associated with a combined OAC (VKA mainly) and AP (aspirin mainly) therapy, without a reduction in risk of recurrence of coronary artery events or thromboembolism. The continuation of an AP in patients on OAC therapy for venous thromboembolism or atrial fibrillation remains a recurrent matter of debate and is still little studied in patients on direct OAC (DOAC). Purpose: Our main objective was to evaluate to what extent combined DOAC-AP therapy met recommendations of current guidelines. A secondary objective was to describe antithrombotic prescription schemes in patients on DOAC with a recent percutaneous coronary intervention (PCI). Material and methods: We performed an observational retrospective cohort study in a 450-bed teaching hospital. Among DOAC patients prospectively reviewed by a clinical pharmacist dedicated to anticoagulation between January and December 2016, we selected patients with a concomitant DOAC and AP prescription during their hospitalisation. Medical history, clinical and medication data were retrieved from the electronic medical record. Based on current guidelines, a decision tool was developed to evaluate the appropriateness of combined DOAC-AP therapy according to three classifications: 'likely appropriate' (i.e. in line with current guidelines); 'out of guidelines'; and 'debatable'. Evaluations were performed first by the clinical pharmacist. Complex cases were then discussed with specialist physicians. Results: Among 336 patients screened, 106 (31%) received combined DOAC-AP therapy during their hospitalisation. Fifty-two prescriptions (49%) were considered as 'likely appropriate', 51 (48%) were rated as 'out of guidelines' (including 27 patients with stable coronary artery disease) and no consensus was achieved for three (3%; judged as 'debatable'). Eighteen patients had undergone a PCI in the past 6 months. The antiplatelet scheme was a combination of aspirin and clopidogrel in 14 (82%) patients and DOAC prescription's adjustment was performed in 10 patients (59%). Conclusion: Half of the patients on DOAC received a potentially unsuitable AP therapy, showing the potential of prescription optimisation. Additional data from clinical trials is also urgently needed, to improve the level of evidence and reinforce the strength of recommendations in clinical guidelines. References and/or acknowledgements: None. No conflict of interest.